Is there any evidence implying the use of a different criterion for protective anti-HBs titer after HBV vaccination in immunosuppressed patients? - Hasanoğlu, İmran; Güner, Rahmet (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Hasanoğlu İ, Güner R. Is there any evidence implying the use of a different criterion for protective anti-HBs titer after HBV vaccination in immunosuppressed patients? Turk J Gastroenterol 2020; 31(4): 346-7.